Vestir para incorporar: a sedução da idéia no design de moda - Menezes, Marizilda dos Santos [UNESP]; Paschoarelli, Luiz Carlos [UNESP]; Rodrigues, Sylvia [UNESP] (My University, 2011)
This article is a reflection on the clothes used as a ideology vehicle, fashion used by groups, tribes, and available to all those who do not belong to those. Since stylists and designers began to get inspirations "on the street", leaving aside the arrogance and restrictions imposed by the major international trends, it’s visible they have been more open to non-Western cultures and cultures from past and present. This generates consumers seeking for more than clothes: they identify and perform a read of author’s (stylist) interpretations, choosing the "ideas" they will wear.

Este artigo faz uma reflexão sobre a roupa consumida como um veículo de ideologias. A moda usada por grupos, “tribos”, e que está ao alcance de todos os que não pertencem a eles. Desde que estilistas e grifes passaram a buscar inspirações “na rua”, deixando de lado a arrogância e as restrições impostas pelas grandes tendências internacionais, nota-se um olhar carregado de referências às culturas não ocidentais e às subculturas passadas e atuais. Os resultados desse novo olhar geram um consumidor que procura mais que roupas: ele identifica e realiza a leitura das interpretações do autor (estilista), escolhendo “as ideias” que vestirá.
Dressing to incorporate: the seduction of the idea in fashion design
Keywords: Fashion design; Subcultures; Trends; Design de moda; Subculturas; Tendências